A Case study on the communication tools of Latter-day Saints employment resource service center - Loreto, Nadine A.
This study explores the effectiveness of communication tools, both PR tools and communication interpersonal tools, in making the clients of a non-profit organization adopt its services. Data were collected through distribution of survey questionnaires and conducting of informal interviews among clients of Later-Day Saint Employment Resource Service Center. Results of the study indicated that PR tools are most effective in creating awareness of the organization. When it comes to giving out detailed information about the center and persuading the clients to use the services of the center, the study found that interpersonal modes of communication are most effective. The study suggest that the center should add a personal touch to their PR tools by covering success stories and employing interpersonal communication tools in their strategies in attracting the attention of its public to use its services. Future researchers are encouraged to conduct the same study with other organizations as well as conduct further investigation on how people decide to accept the services of the same center through studying how its public perceived the image of the center.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication